Migration Dynamics and Humanitarian Governance: A Comprehensive Analysis of the U.S.-Mexico Border Crisis - Ramos García, José María; Ramos Valencia, Jimmy Emmanuel (Razón Crítica, 2025)
This article investigates the complex dynamics of migration and humanitarian governance at the U.S.-Mexico border, specifically at the northern Mexican cities of Tijuana, Nogales, Ciudad Juárez, and Piedras Negras. The study presents detailed data from the U.S. Customs and Border Protection (USCBP), which include 6.83 million encounters with irregular migrants from January 2021 to October 2023. The article highlights the influence of recent U.S. migration policies, particularly under President Biden’s administration, and the challenges faced by the American government in managing the surge in migration flows. Additionally, it analyses the critical role of civil society organizations, the limitations of shelters, and the need for coordinated efforts among governments, NGOs, and international agencies. By analyzing the obstacles related to humanitarian governance, including security concerns, limited resources, and cross-border cooperation, the study contributes to the broader discussion on migration, advocating for a balanced, humane approach that integrates human rights and security measures in border management strategies.